Positive solutions for Hadamard-type fractional differential equations with nonlocal conditions on an infinite interval - Zhai, Chengbo; Liu, Rui (Nonlinear Analysis: Modelling and Control, 2024)
The purpose of this paper is to analyse the local existence and uniqueness of positive solutions for a Hadamard-type fractional differential equation with nonlocal boundary conditions on an infinite interval. The technique used to arrive our results depends on two fixed point theorems of a sum operator in partial ordering Banach spaces. The local existence and uniqueness of positive solution is given, and we can make iterative sequences to approximate the unique positive solution. For the illustration of the main results, we list two concrete examples in the last section.